AKURASI PENINGKATAN PROSTATE-SPECIFIC ANTIGEN DALAM DARAH TERHADAP KEGANASAN PROSTAT - Daniel Mahendra Krisna; Hariatmoko Hariatmoko; Rizaldy Taslim Pinzon (Faculty of Medicine, Universitas Islam Indonesia, 2018)
Background: Various controversies arose in the study of PSA examination as an alternative of biopsy to detect prostate malignancy. Prostate Specific Antigen (PSA) is a specific protein secreted by the prostate gland and is affected by various conditions. PSA levels will certainly increase at the enlargement of the prostate gland. An accurate cutoff point that can detect prostate cancer is needed.Objective: To evaluate the PSA diagnostic test against prostate malignancy.Methods: This study used a diagnostic test method for 91 patients undergoing either prostate gland surgery or open prostatectomy at Bethesda Hospital Yogyakarta in January 2014-January 2016 period. Data were taken from medical records with inclusion criteria as follow: over 50 years of age, preoperative PSA, and PA results. This study was a descriptive analytic study. In the diagnostic test AuROC, cutoff points were determined. Chisquare test was performed to assess sensitivity, specificity, PPV, NPV, LHR -, and LHR +.Results: We studied 91 patients with a mean age of 70.24 ( 46-54 ) and mean PSA level of 27.2 ( 0.59-101 ). The results of PA prostate tissue examinations were adenocarcinoma in 15 patients ( 16.5 % ) and BPH in 76 patients ( 83.5 %) On all PSA levels, AuROC were 0.90. Specificity of PSA with 4 ng / mL cutoff, 10 ng / mL, 20 ng / mL, 50 ng / mL, and 100 ng / mL were 0.53, 35.53, 67.11, 96.05, 98.68. When the cutoffs were reduced to 4.01-10ng/mL, 10.01-20 ng/mL, 20.01-50ng/ mL,50.01-100 ng/mL, and > 100 ng/mL, the specifity were 76.32, 68.00, 69.74, 96.05, 100.00. Cutoff value of 50ng / mL had LHR + >10.00 ( 15:20 ).Conclusion: There is a strong correlation between PSA and prostate malignancy. PSA value> 50 ng / mL has high accuracy to detect prostate malignancy. A biopsy is needed to determine a definitive diagnostic because no cutoff value can be used as a benchmark.